Pemanfaatan, Toksisitas dan Glikosida Jantung dari Digitalis purpurea L - Marina Silalahi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Digitalis purpurea (Schrophulariaceae) is used by the local Indonesian community as an ornamental plant, even though this plant has high toxicity and has the potential to treat heart problems. This study aims to explain the botany, bioactivity and toxicity of D. purpurea based on literature studies. Literature was obtained online, especially Google scholar using the keywords Digitalis purpurea, bioactivity D. purpurea, and glycoside heart. In Europe, D. purpurea is very popular to treat congestive heart failure and has been used since 200 years ago, but it is very toxic to humans. Digitalis poisoning causes anorexia, nausea, vomiting, and diarrhea, yellow or jaundice vision, appearance of blurred lines, decreased heart rate, and weight loss. D. purpurea's bioactivity includes overcoming heart failure, antioxidants, anti-cancer/tumor. Cardiac glycosides present in D. purpurea include cardenolides, digitoxin, gitoxin, purpureaside A, purpureaside B, acteoside and purpureaside C, which are related to their bioactivity. The toxicity and inotropic effects of cardiac glycosides result directly from inhibition of membrane-bound Na+K+_ATPase, an enzyme involved in the transport of Na+K+ across cell membranes. The use of D. purpurea needs strict control so that side effects can be minimized.